MOA-2010-BLG-523: "failed planet" = RS CVn STAR - Gould, A.; Yee, J.; Bond, I.; Udalski, A.; Han, C.; Jorgensen, U.; Greenhill, J.; Tsapras, Y.; Pinsonneault, M.; Bensby, T.; Allen, W.; Almeida, L.; et al. (Institute of Physics Publishing, 2013)
The Galactic bulge source MOA-2010-BLG-523S exhibited short-term deviations from a standard microlensing light curve near the peak of anAmax ~ 265 high-magnificationmicrolensing event. The deviations originally seemed consistent with expectations for a planetary companion to the principal lens. We combine long-term photometric monitoring with a previously published high-resolution spectrum taken near peak to demonstrate that this is an RS CVn variable, so that planetary microlensing is not required to explain the light-curve deviations. This is the firstspectroscopically confirmed RS CVn star discovered in the Galactic bulge.